The culture of surveillance discipline and social control in the United States - Staples, William G. (Contemporary social issues, 1997)
This book takes a look at the many ways in which people are being monitored and controlled in everyday life. The author looks at some issues of social control, from surveillance cameras to lie-detector tests to drug testing, and the questions that arise about freedom, privacy, and the power of the state and private organizations.